Distinguishing the Associations Between Evening Screen Time and Sleep Quality Among Different Age Groups: A Population-Based Cross-Sectional Study - Sun, Long; Li, Keqing; Zhang, Lili; Zhang, Yunshu (Frontiers in Psychiatry, 2022)
Objective The age differences in the association between screen time and sleep problems have been implied in many studies, and this study aims to distinguish the associations between evening screen time and sleep quality among different age groups. Methods This is a population-based, cross-sectional study among community residents aged ≥18 years in China. A total of 21,376 valid questionnaires were analyzed. Sleep quality was measured by the Pittsburgh Sleep Quality Index. Averaged evening screen time (AEST), sociodemographic information, and health-related behaviors were also evaluated in this study. Results In the 18-to-34-year age group, compared with people without AEST, ≤1 h/day (β = 0.34, p < 0.05) and >3 h/day (β = 1.05, p < 0.001) of AEST were significantly associated with poor sleep quality, and a reverse S-shaped relationship for this association was shown. In the 35-to-49-year and 50-to-64-year age groups, ≤1 h/day (β = 0.43 and 0.36, both p < 0.001), ≤2 h/day (β = 0.43 and 0.31, p < 0.001 and p < 0.01), ≤3 h/day (β = 0.62 and 0.61, both p < 0.001), and >3 h/day (β = 1.55 and 1.88, both p < 0.001) of AEST were positively associated with poor sleep quality. In the 65-year-and-older age group, a J-shaped relationship was found, and ≤3 h/day (β = 0.82, p < 0.001) and >3 h/day (β = 1.84, p < 0.001) of AEST were associated with poor sleep quality. Conclusion Associations between AEST and sleep quality among different age groups are different. In the 18-to-34-year and 65-year-and-older age groups, acceptable AEST is not related to sleep quality. In the 35-to-49-year and 50-to-64-year age groups, AEST was harmful to sleep quality.